The Influence of Elastic Taping on Dynamic Muscular Control (Dynamic Control Ratio) Evertor-Invertor Ankle in Type 2 Diabetes Mellitus Male with Complications of Peripheral Neuropathy - Yuli Indah Kurnia; Imam Subadi; I Putu Alit Pawana; Sony Wibisono (Surabaya Physical Medicine and Rehabilitation Journal, 2020)
Background: Type 2 Diabetes Mellitus (DM) with Peripheral Neuropathy often have impared control of muscle strength that increases the risk of fall. Elastic taping (ET) is a special elastic band that can stretch up to 140% and could facilitate muscle contraction.Aim: To prove the influence of ET on the dynamic muscular control balance between evertor and invertor muscles of the ankle in type 2 DM male with peripheral neuropathy.Material and methods: This study used a pre-post one grup study, with10 type 2 DM male with peripheral neuropathy. All subjects were examined for ankle evertor-invertor dynamic control ratio (DCR) with isokinetic dynamometer at 600/sec and 1200/sec before elastic taping (ET), 30 minutes after ET, at the third day of ET aplication and 3 days after ET was released. Elastic taping was applied with functional tehniques on the both ankles.Result: There were no significant differences between with and without the application of KT in the ankle evertor-invertor DCR in both side. The p value were same in both sides, at 600/sec after 30 minute ET (p=0.72), at the third day of ET aplication (p=0,24), 3 days after released ET (p= 0,88) and at 1200/sec after 30 minute ET (p=0,17).Conclusion: Elastic taping did not improve the ankle evertor-invertor DCR in type 2 DM male patients with peripheral neuropathy.